A child feeding a child: Early mother's marriage and child growth in India - Amal Ahmad; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2024)
Hundreds of millions of Indian children are too short for their age. In this paper we explore whether early marriage of women in India contributes to this phenomenon. Using India's national health surveys and age at menarche as an instrument, we find that one year earlier mother's marriage reduces her child's height-for-age by 0.20 standard deviations. On mechanisms, earlier-married mothers delay infant complementary feeding and breastfeed for less time; these practices appear to be influenced by knowledge gaps and preference issues. Given slow evolution in marital age practices, supporting the nutrition efforts of earlymarried mothers can markedly improve intergenerational well-being.
Keywords: I12; J12; O15; 330; Early marriage; child growth; health behavior; rural development